Degradation of antibiotic ciprofloxacin by different AOP systems using electrochemically generated hydrogen peroxide - Lima, Veronica B.; Goulart, Lorena A.; Rocha, Robson S.; Steter, Juliana R.; Lanza, Marcos R.V. [UNESP] (My University, 2020)
The present work reports the degradation of the antibiotic ciprofloxacin (CIP) by different advanced oxidative process systems (UV; Anodic Oxidation; H2O2; H2O2/UV; H2O2/Fe2+ and H2O2/UV/Fe2+) in an electrochemical cell using gas diffusion electrode (GDE) for the synthesis of hydrogen peroxide. CIP degradation and mineralization were evaluated by high efficiency liquid chromatography (HPLC) and total organic carbon (TOC) techniques. Of all the systems investigated, the photoelectro-Fenton system presented the best degradation efficiency; this system promoted highly significant mineralization percentages of 54.8% and 84.6% in 90 and 360 min, and relatively lower energy consumption rates of 4110.0 and 9808.2 kWh kg−1 TOC, respectively. In 6 h period of experiment, the main degradation products of ciprofloxacin were identified, and the aliphatic acids obtained helped confirm the rupture of the aromatic ring. The application of the photoelectro-Fenton process with in situ eletroctrogeneration of H2O2 using GDE has proved to be suitably promising for the treatment of organic pollutants.
Keywords: Ciprofloxacin; Fenton processes; Gas diffusion electrode; Hydrogen peroxide